COMPOSITE POLYMER SUSPENSIONS WITH COMPLEX PARTICLE MORPHOLOGY - N. I. Prokopov; I. A. Gritskova; A. Yu. Gervald; M. S. Balashov (Российский технологический журнал)
The review is dedicated to the synthesis of composite polymer suspensions with complex particle morphology. Authors attempted to summarize effects of polymerization conditions on particle morphology. The significance of further investigations in the field of composite polymer suspensions synthesis was shown. The main aspects of different monomers emulsion homopolymerization, affecting the polymer particle morphology, such as polymerization topochemistry, free energy of particle formation, the kind of monomer and others were discussed. The determination methods of polymer particles phase structure may be shown to be classified as direct and indirect. The most frequently used investigation methods of suspension particles morphology viz electron microscopy, soap titration technique and film forming were described. General techniques of composite polymer particle synthesis, such as emulsion copolymerization and seed polymerization, were given and considered in detail. Advantages and disadvantages of each method were listed. Determination of particle morphology, using thermodynamic approach, was discussed. Obtained composite polymer particles were found to be classified into two large groups: non-uniform composite gradient particles and heterophase particles.